ASSESSMENT OF THE COMPETITIVENESS OF HOTEL AND RESTAURANT INSTITUTIONS OF KRYVY RIG - NIKOLAICHUK, OLHA; IVANAGA, VICTORIA; LAPTEVA, ANNA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of the study is to assess the competitiveness of hotels and restaurants in the regional market of Kryvyi Rih.  The competitiveness of hotel and restaurant establishments in the regional market of Kryvyi Rih is analyzed. The analysis was conducted according to the following criteria: range of additional services, design, pricing policy, food outlets, availability of loyalty programs, level of service, location. A comparative analysis of the number of research institutions was conducted. It is established that the largest range of rooms among the analyzed. establishments in Kryvyi Rih has "Reikartz Aurora Kryvyi Rih". In terms of the number of rooms, the market leaders are Park House, Druzhba and Reikartz Aurora Kryvyi Rih. An analysis of the pricing policy of institutions. Significant differentiation of prices in the market of hotel services in Kryvyi Rih has been established. The cost of rooms in hotels that are part of the national hotel and restaurant chain "Reikartz" ("Reikartz Aurora Kryvyi Rih", "Optima Deluxe Kryvyi Rih", "Raziotel Kryvyi Rih") includes the cost of breakfast. in Druzhba and MIZAR Hotel & Restaurant the cost of meals is paid by the guest separately. In the hotel complex "Park House", depending on the category of rooms, the cost of breakfast is included in the price of accommodation only in more expensive rooms. Analysis of the competitiveness of institutions according to guest reviews showed that the highest score is "Park House. MIZAR Hotel & Restaurant and Druzhba have high marks. According to guests, Reikartz Aurora Kryvyi Rih has an overall score of 8.4 points and is inferior to competitors in most criteria: staff, value for money, comfort, convenience, cleanliness, free WI-FI. For further development of competitive advantages of the analyzed institutions, measures to expand the range of additional services, optimize pricing policy and constantly improve the quality of services provided are relevant.
Keywords: competitiveness; hotel and restaurant establishments; market of hotel and restaurant services